Executive compensation, firm ownership and corporate governance in China - Zheng, Xue (2019)
This article explores executive compensation, firm ownership structure and corporate governance by using the corporations that listed in Shanghai and Shenzhen stock exchanges in China. First of all, I describe the changes in the Chinese market over the past few decades and the unique characteristics of companies in China. Then, this research develops a model about CEO pay based on the null hypotheses to measure the relationship between executive payment and corporate governance. Consistent with agency theory, I find that CEO income and company performance have a positive correlation. It means executives are vulnerable to rewards when a company has a good operating profit. Research also shows that the CEO pay will rise when outside investors have more equity, or the ownership of the company is more concentrated. State ownership would harm managers pay. However, the effect of board structure on executive compensation is not as evident as it might seem. The proportion of non-executive directors on the board and the duality of CEO would not affect executive payment significantly. Only board size has a positive influence on managers pay. Finally, through analyzing the empirical results, this article puts forward some suggestions. More in-depth researches need to be done in the future.